2019
DOI: 10.3389/fimmu.2019.01138
|View full text |Cite
|
Sign up to set email alerts
|

A β2-Integrin/MRTF-A/SRF Pathway Regulates Dendritic Cell Gene Expression, Adhesion, and Traction Force Generation

Abstract: β2-integrins are essential for immune system function because they mediate immune cell adhesion and signaling. Consequently, a loss of β 2 -integrin expression or function causes the immunodeficiency disorders, Leukocyte Adhesion Deficiency (LAD) type I and III. LAD-III is caused by mutations in an important integrin regulator, kindlin-3, but exactly how kindlin-3 regulates leukocyte adhesion has remained incompletely understood. Here we demonstrate that mutation of the kindlin-3 binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…As transcription factors play critical roles in the regulation of gene expression, it is not surprising that alterations in the expression or activity of key transcription factors have been linked to the development of several cancers [ 40 ]. While it has long been known that signaling downstream of integrins can influence gene expression through the regulation of transcription [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], roles for distinct integrins in the regulation of specific transcription factors remain underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…As transcription factors play critical roles in the regulation of gene expression, it is not surprising that alterations in the expression or activity of key transcription factors have been linked to the development of several cancers [ 40 ]. While it has long been known that signaling downstream of integrins can influence gene expression through the regulation of transcription [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], roles for distinct integrins in the regulation of specific transcription factors remain underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…MKL1 also regulated expression of genes involved in interferon signaling, such as STAT1 and several IFIT genes, but MKL1 deficiency also resulted in the upregulation of several genes ( 11 ). We have recently shown that in murine dendritic cells, MKL1 deletion did not only impact expression of cytoskeletal genes and genes of cytoskeletal regulators ( Fgr, Hck, Stmn1, Ckap2l, Anln, Tpm2, Tubb5 ), but also genes encoding for proteins involved in many other cellular pathways, such as lipid metabolism ( 12 ). Therefore, the effect of MKL1 on gene expression in immune cells appears to be cell type-specific.…”
Section: The Mkl1/srf Pathwaymentioning
confidence: 99%
“…The role of MKL1 in dendritic cell adhesion and migration has also been investigated. Interestingly, the MKL1/SRF pathway is downstream of beta2-integrins and beta2-integrin-mediated RhoA activation and F-actin polymerization in murine leukocytes ( 12 ). 3D migration of MKL1 knockout dendritic cells in response to CCL19 was normal, while (static) adhesion to integrin ligands was slightly reduced.…”
Section: Role Of Mkl/srf Signaling In Leukocyte Adhesion and Migratiomentioning
confidence: 99%
“…The major signal transduction pathways activated by the integrins include the Janus kinase/signal transducers and activators of transcription (JAK/STAT) [ 331 ], mitogen-activated protein kinase (MAPK) [ 332 ], and phosphoinositide-3-kinases/protein kinase B (PI3K/AKT) pathways [ 333 , 334 ]. More recently, the β2 integrin subunit from the immune cells was also identified as an upstream regulator of the actin-regulated myocardin-related transcription factor A/serum response factor (MRTF-A/SRF) pathway in response to external cell stimuli that initiate F-actin polymerization downstream of RhoA activation [ 335 ]. However, in corneal wound healing, little is known about which pathway contributes the most to the healing process.…”
Section: The Future Of the Htec: Potential Applications And Usesmentioning
confidence: 99%